2017
DOI: 10.1111/epi.13783
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory targets and treatments for epilepsy validated in experimental models

Abstract: A large body of evidence that has accumulated over the past decade strongly supports the role of inflammation in the pathophysiology of human epilepsy. Specific inflammatory molecules and pathways have been identified that influence various pathologic outcomes in different experimental models of epilepsy. Most importantly, the same inflammatory pathways have also been found in surgically resected brain tissue from patients with treatment-resistant epilepsy. New anti-seizure therapies may be derived from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 91 publications
5
125
0
8
Order By: Relevance
“…FIRES is a condition that may be sustained by brain inflammation, possibly as mirror focus of a systemic inflammatory response to a common infection in predisposed patients. In support, neuroinflammation in animal models is associated with long‐term reduction in seizure threshold together with lasting alterations of brain physiology and gene expression . Moreover, specific antiinflammatory drugs reduce ongoing seizures and inhibit epileptogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FIRES is a condition that may be sustained by brain inflammation, possibly as mirror focus of a systemic inflammatory response to a common infection in predisposed patients. In support, neuroinflammation in animal models is associated with long‐term reduction in seizure threshold together with lasting alterations of brain physiology and gene expression . Moreover, specific antiinflammatory drugs reduce ongoing seizures and inhibit epileptogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…In support, neuroinflammation in animal models is associated with long-term reduction in seizure threshold together with lasting alterations of brain physiology and gene expression. 12,13 Moreover, specific antiinflammatory drugs reduce ongoing seizures and inhibit epileptogenesis. 13 Early brain biopsy is performed rarely, but it could help to clarify FIRES pathogenesis: as in our case, brain biopsy indicated a sustained activation of the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent up‐regulation of chemokines attract inflammatory monocytes to the CNS that contribute to neuronal death and seizure onset . Alternatively, cytokines and chemokines may interact with neurons and/or astrocytes to directly modulate synaptic activity . It is likely that there is no single molecular event that entirely accounts for the effects of neuroinflammation on seizure risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that epileptogenesis could start as soon as the SE begins (Bumanglag and Sloviter, 2008; Sloviter, 2008; Loscher and Brandt, 2010). The hyperexcitability of neurons, manifested by epileptiform spiking, occurring during SE triggers series of overlapping molecular and cellular changes in the brain (Aronica et al, 2017; Barker-Haliski et al, 2017; Klee et al, 2017). In the rat and mouse kainate models, though the behavioral seizures stopped after the diazepam treatment, the electrographic seizures persisted for several hours (Fig.…”
Section: The Hallmarks Of Epileptogenesismentioning
confidence: 99%